Utilization and expenditure of Indonesia National Health Insurance before and during COVID-19 pandemic in Indonesia: a descriptive study - Hafidz, Firdaus; Kusila, Gilbert Renardi; Nadhira, Farrasila; Daniel; Baros, Wan Aisyah; Revelino, Dedy; Dhanalvin, Erzhan; Saut, Benjamin; Jaya, Citra; Oktavia, Ayunda (BKM Public Health and Community Medicine, 2022)
Purpose: This study describes the utilization of healthcare facilities before and during the COVID-19 pandemic and the expenditure of national health insurance at primary and secondary healthcare facilities. Methods: This is a descriptive study with a cross-sectional design. We utilized claim data from the National Health Insurance from January 2018 to June 2021. The population included in this study were all Indonesian citizens who contracted COVID-19. Both the Ministry of Health and National Health Insurance expenditure for COVID-19 services were captured. The data were analyzed in frequency and proportions. Results: There was a consistent utilization trend across all types of healthcare facilities (primary vs. secondary; public vs. private), with an upward trend before the Covid-19 pandemic, a downward trend in 2020, and a slight increase before June 2021. Primary healthcare utilization jumped by 19% during the 2018-2019 period and dropped by 34% from March to April 2020. A similar trend was observed in the secondary healthcare facilities, with the utilization cost being lower in the 2020 and 2021 periods than in previous years. Hospital visits also showed a decreasing trend during the start of the pandemic (both public and private-owned), which was linear to the expenditure of inpatient and outpatient visits. The total claim for COVID-19 health care increased to IDR 77.8 trillion by August 2021 (inpatient and outpatient), with the highest cost per patient for inpatients with comorbidities. Conclusion: Healthcare utilization decreased significantly during the COVID-19 pandemic period. On the other hand, since COVID-19 increased expenditure, particularly due to inpatient services and comorbidities, National Health Insurance needs to prepare a health financing strategy to anticipate the shift of financing in time of the endemic.